(untitled) (Scientific journal of the Fergana State University, 2024)
This article examines the impact of contemporary teaching methods on foreign language acquisition. It highlights various modern pedagogical approaches, including communicative language teaching, task-based learning, and the use of technology-enhanced instruction. The study explores how these methods enhance language proficiency, learner engagement, and cultural competence. By analyzing recent research and case studies, the article provides insights into the effectiveness of innovative teaching strategies in diverse educational settings. It also discusses the challenges and potential solutions in implementing these methods, offering practical recommendations for educators to optimize language learning outcomes. This study aimed to evaluate the effects of contemporary teaching methods on foreign language acquisition. Data were collected from a mixed-methods approach, incorporating quantitative assessments and qualitative feedback from students and instructors across multiple educational settings. The teaching methods analyzed included Communicative Language Teaching (CLT), Task-Based Language Teaching (TBLT), Technology-Enhanced Language Learning (TELL), and immersive learning environments. The results of this study indicate that contemporary teaching methods significantly improve foreign language acquisition compared to traditional approaches.